Intersectin associates with synapsin and regulates its nanoscale localization and function - Gerth, Fabian (Proc Natl Acad Sci U S A, 2017)
Neurotransmission is mediated by the exocytic release of neurotransmitters from readily releasable synaptic vesicles (SVs) at the active zone. To sustain neurotransmission during periods of elevated activity, release-ready vesicles need to be replenished from the reserve pool of SVs. The SV-associated synapsins are crucial for maintaining this reserve pool and regulate the mobilization of reserve pool SVs. How replenishment of release-ready SVs from the reserve pool is regulated and which other factors cooperate with synapsins in this process is unknown. Here we identify the endocytic multidomain scaffold protein intersectin as an important regulator of SV replenishment at hippocampal synapses. We found that intersectin directly associates with synapsin I through its Src-homology 3 A domain, and this association is regulated by an intramolecular switch within intersectin 1. Deletion of intersectin 1/2 in mice alters the presynaptic nanoscale distribution of synapsin I and causes defects in sustained neurotransmission due to defective SV replenishment. These phenotypes were rescued by wild-type intersectin 1 but not by a locked mutant of intersectin 1. Our data reveal intersectin as an autoinhibited scaffold that serves as a molecular linker between the synapsin-dependent reserve pool and the presynaptic endocytosis machinery.